Implementation of a precise quadrature point bias controller to the integrated intensity electro-optic modulator - Svarny, J. (2012 13th Biennial Baltic Electronics Conference, 2012)
A broadband electro-optic modulating unit forms a key part of a specialized transmission system for needs of measurements. The modulating unit is based on an integrated analog intensity modulator of Mach-Zehnder type. A proper adjustment of modulator operating point significantly affects performance of the modulator and consequently of the whole transmission system as well. The paper deals with design and implementation of a specialized driver - a bias circuit for extremely precise set-up of optimal operating point of the modulator. The driver operates on principle of suppression of second harmonic component detected at the modulator output during excitation of bias port with a low-frequency harmonic signal.